Enhanced recovery in intestinal surgery. Issue 3 (March 2017) - Koh, Hoey C.; Horgan, Alan F.
Abstract: Enhanced recovery after surgery (ERAS) programmes utilise a multi-modal and multidisciplinary approach to surgical care. The aim of ERAS is to reduce the surgical stress response, maintain physiological function and metabolic homeostasis and expedite patients' recovery to their baseline status. With its success in colorectal practice, ERAS is increasingly adopted in other surgical specialities. A good ERAS programme involves integrated pre-operative, intra-operative and post-operative evidence-based practice. Successful ERAS programme translates to a standardized patient care pathway, improved clinical outcomes and shorter hospital stay, all of which will help facilitate the increasing demand on healthcare and bed pressure. Its principles and many components are transferable to other surgical specialities including acute surgical services and medical specialities to improve patient care and recovery and will soon become the standard of care for the majority of hospital inpatients.